2020
DOI: 10.7554/elife.59157
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of peripheral nervous system formation mechanisms in divergent ascidian embryos

Abstract: Ascidians with very similar embryos but highly divergent genomes are thought to have undergone extensive developmental system drift. We compared, in four species (Ciona and Phallusia for Phlebobranchia, Molgula and Halocynthia for Stolidobranchia), gene expression and gene regulation for a network of six transcription factors regulating peripheral nervous system (PNS) formation in Ciona. All genes, but one in Molgula, were expressed in the PNS with some differences correlating with phylogenetic distance. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(55 citation statements)
references
References 80 publications
(155 reference statements)
1
46
0
Order By: Relevance
“…We first determined whether gene expression was conserved in the model species that we have used here, namely the ascidian Phallusia mammillata and the European amphioxus B. lanceolatum . In C. intestinalis , the dynamic of expression for TFs and signaling molecules in the vPNS is as follows [ 27 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first determined whether gene expression was conserved in the model species that we have used here, namely the ascidian Phallusia mammillata and the European amphioxus B. lanceolatum . In C. intestinalis , the dynamic of expression for TFs and signaling molecules in the vPNS is as follows [ 27 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From tailbud stages, Dlk , Pou4 , Myt1 , Atoh1/7 , Atoh8 , Celf3/4/5/6 and Slc17a6/7/8 (also known as Vglut ) are expressed in both dorsal and ventral ESNs. We have previously shown that several neurogenic midlines and ESNs markers have a conserved expression in P. mammillata [ 27 ]. Here, we report the expression of additional orthologous genes in Phallusia (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations